Study of the interactions between emulsion flow and a spectrometer probe based on numerical simulations. - Grosche, Lucas Caetano (2013)
In the present work, the flow behavior of an oil-in-water emulsion around and inside the measurement chamber of an in-line optical sensor probe is studied. The emulsion consists of a metalworking fluid, with oil droplets diameter ranging from 100 nanometers to 100 micrometers. The design of the UV-Vis light spectrometer probe is in accordance with the concept proposed in the research project named EPM (Emulsion Process Monitor in Metalworking Processes), carried out within the scope of the BRAGECRIM program between the University of São Paulo and the University of Bremen. This study is based on the numerical simulation of the interactions between the emulsion and the measurement system using computational fluid dynamic techniques, and is aimed at evaluating the effects of the probe geometry, its position relative to the flow field, and fluid properties on the expected spectrometer readings. Such effects are correlated with changes in droplet concentration and or droplet size segregation inside the measurement chamber of the optical probe, which can cause changes in the scattered light intensity readings. Segregation effects due to flow disturbances around the probe can be neglected under normal measurement conditions, with the probe facing the slit area inlet against the flow stream. Based on the simulation results, even if the probe is misplaced, the effect on the measurements is still insignificant. In-situ measurements carried out in a laboratory set up installed in the injection tube of a drilling machine support the simulation results, since no segregation effect related to the measurement system was observed. In addition to the study, the possibility of bacteria attachment on the internal glass walls of the probe was evaluated and it was found that when the flow velocity is large enough to produce a wall shear stress of about 3-5 Pa the bacterial contamination may be avoided. Changes in the probe geometry are proposed in order to attain an isokinetic condition for the flow around and inside the probe, resulting in a higher wall shear stress for lower inlet flow velocities. An additional study was performed using a tracking particle model to understand the relevance of the individual particles behavior under different flow conditions. The results do not indicate any significant effect on the measurements inside the probe, although additional studies should be carried out in this topic by considering a population balance model for the oil droplets.